The role of Pd-In interactions on the performance of PdIn-Hmordenite in the SCR of NOx with CH4 - Decolatti, Hernán Pablo (2011)
The aims of this work were to use several techniques to characterize the generated species when indium and palladium were successively exchanged in H-mordenite and to investigate the effect of the Pd/In ratio on the said species as well as to correlate the activity of the prepared solids with the formed moieties. We studied the activity of In-Hmordenite catalysts obtained by reductive solid-state ion exchange and the effect of the addition of Pd. There was a clear correlation between the maximum catalytic activity of each catalyst and its ability to form NO2 in the temperature-programmed desorption of NO (NO-TPD) experiments performed after NO adsorption. PdInHM(1/3) was the catalyst that showed the best results in activity and, after the first catalytic test, it was further activated. The temperature-programmed reduction (TPR) and NO-TPD results of this solid suggest that the amount of active species increased after the reaction and that there would be some kind of Pd-In interaction. The characterization of the fresh and used samples by CO adsorption and FTIR shows the differences between PdInHM(1/3) and PdInHM(1/6) catalysts in terms of how Pd was present on the support, and justifies the different catalytic behavior of both catalysts.